1, 10‐Phenanthroline Ruthenium(II) Complexes as Model Systems in the Search for High‐Performing Triplet Photosensitisers: Addressing Ligand versus Metal Effects. Issue 12 (6th October 2017) - Lu, Yue; Conway‐Kenny, Robert; Twamley, Brendan; McGoldrick, Niamh; Zhao, Jianzhang; Draper, Sylvia M.
Abstract: A series of Ru II complexes containing extended 1, 10‐phenanthroline ligands with triphenylamine (TPA) and/or pyrene as light‐harvesting chromophores, were synthesised and investigated in triplet photosensitising applications. "Chemistry‐on‐the‐complex" methods were employed using Sonogashira cross‐coupling reactions. Tunable absorption and triplet lifetimes were achieved depending on the type and number of the chromophores. Intense absorption in the visible region was common to the generated complexes. Those Ru II complexes containing only TPA appendages showed much shorter triplet lifetimes ( τ T <0.6 μs) than those containing pyrene ( τ T up to 148 μs). The complexes were explored as triplet photosensitisers for singlet‐oxygen ( 1 O2 ) photosensitisation and triplet–triplet annihilation based upconversion applications. The best performing complex, Ru‐5, with a single pyrene chromophore, displayed the highest 1 O2 quantum yield ( Φ Δ =84.4 %) and an attractive upconversion quantum yield ( Φ UC =14.7 %). A comparison of the results with those of analogous Ir III complexes comprising the same large N^N coordinating ligands showed that both sets of complexes exhibit the same ligand‐dependent trends in behaviour. The implication is that synthetically accessible Ru II complexes might be effective model systems for predicting those ligand frameworks likely to give the highest performing Ir III ‐based triplet photosensitisers. Abstract : Model behaviour : The triplet–triplet annihilation upconversion and singlet oxygen quantum yields of two series of transition metal complexes (Ru II and Ir III ) are compared. In both series, the ligands are based on extended 1, 10‐phenanthroline substituted at the 3 or 3, 8 positions with a different chromophore.